Phytosterols from the seeds of petai (Parkia Speciosa) - Lai, Jin Frve (2012)
Steroids are found in plants, animals and fungi. All steroids are made in cells either from the sterols lanosterol (animals and fungi) or from cycloartenol (plants). Both lanosterol and cycloartenol are derived from the cyclization of the triterpene squalene. Triterpenes are terpenes consisting of six isoprene units and have the molecular formula C3017148 (e.g carotenoids). The steroids derived from animal are the cholesterol while the steroids derived from plant is the phytosterols. There are more than 100 types of phytosterols have been reported in plant species, but the more abundant are sitosterol, stigmasterol and campesterol. The importance of phytosterols is their contribution towards lowering body cholesterol. Cholesterol is transported in blood in the form of lipoprotein which includes the high density (HDL) and low density (LDL) lipoproteins where LDL is the bad cholesterol. Too much LDL cholesterol in the blood can cause cholesterol to build up in the artery walls, leading to the narrowing of the arteries, Atherosclerosis. Thus dietary cholesterol intake is reduced in patients with such disease. Another way to reduce blood cholesterol is to consume phytosterols which compete with cholesterol absorption. The objective of this project is to find the new sources of phytosterols from plant found in Malaysia. The plant use in this project is Petai (Panda speciosa). Petai is an edible legume, the seeds of which are already consumed in Malaysia as a minor vegetable. Although many legumes have been studied as sources of phytosterols very little is reported on Petai. The practical study is carry out by using extraction to extract phytosterols from Petai and chromatographic and spectrophotometric method to separate and identify the extracted phytosterols. Petai is a legume. Legumes like soybean are known to be rich in phytosterols.